β-lactamase-mediated resistance in MDR-Pseudomonas aeruginosa from Qatar - Mazen A. Sid Ahmed (18810337) (2020)
Background The distribution of β-lactam resistance genes in P. aeruginosa is often closely related to the distribution of certain high-risk international clones. We used whole-genome sequencing (WGS) to identify the predominant sequence types (ST) and β-lactamase genes in clinical isolates of multidrug-resistant (MDR)-P. aeruginosa from Qatar Methods Microbiological identification and susceptibility tests were performed by automated BD Phoenix™ system and manual Liofilchem MIC Test Strips. Results Among 75 MDR-P. aeruginosa isolates; the largest proportions of susceptibility were to ceftazidime-avibactam (n = 36, 48%), followed by ceftolozane-tazobactam (30, 40%), ceftazidime (n = 21, 28%) and aztreonam (n = 16, 21.3%). All isolates possessed Class C and/or Class D β-lactamases (n = 72, 96% each), while metallo-β-lactamases were detected in 20 (26.7%) isolates. Eight (40%) metallo-β-lactamase producers were susceptible to aztreonam and did not produce any concomitant extended-spectrum β-lactamases. High risk ST235 (n = 16, 21.3%), ST357 (n = 8, 10.7%), ST389 and ST1284 (6, 8% each) were most frequent. Nearly all ST235 isolates (15/16; 93.8%) were resistant to all tested β-lactams. Conclusion MDR-P. aeruginosa isolates from Qatar are highly resistant to antipseudomonal β-lactams. High-risk STs are predominant in Qatar and their associated MDR phenotypes are a cause for considerable concern. Other Information Published in: Antimicrobial Resistance & Infection Control License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1186/s13756-020-00838-y